2002
DOI: 10.1002/pds.721
|View full text |Cite
|
Sign up to set email alerts
|

Moderate alcohol consumption and adverse drug reactions among older adults

Abstract: Moderate alcohol intake is associated with an increased risk of ADRs; this effect seems more evident among women than men, and it does not differ across age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 42 publications
2
71
0
1
Order By: Relevance
“…A third study among a sample of 667 communitydwelling older adults (mean [SD] age, 74 [7] years) living in northeast New York estimated that 25% of them drank alcohol and took medication that could negatively interact with alcohol [67]. A fourth study, using data from the Italian Group of Pharmacoepidemiology in the Elderly study, found that the prevalence of adverse drug reactions among 22,778 older hospitalized persons (mean [SD] age, 70 [16] years) was 3.7% among abstainers and 4.1% among those who drank < 40 g of alcohol per day [68]. After adjusting for potential confounders, moderate drinkers were 24% more likely to experience an adverse drug reaction compared with abstainers.…”
Section: Interaction With Medicationsmentioning
confidence: 99%
“…A third study among a sample of 667 communitydwelling older adults (mean [SD] age, 74 [7] years) living in northeast New York estimated that 25% of them drank alcohol and took medication that could negatively interact with alcohol [67]. A fourth study, using data from the Italian Group of Pharmacoepidemiology in the Elderly study, found that the prevalence of adverse drug reactions among 22,778 older hospitalized persons (mean [SD] age, 70 [16] years) was 3.7% among abstainers and 4.1% among those who drank < 40 g of alcohol per day [68]. After adjusting for potential confounders, moderate drinkers were 24% more likely to experience an adverse drug reaction compared with abstainers.…”
Section: Interaction With Medicationsmentioning
confidence: 99%
“…The article concludes with the idea that even though pharmacists are aware of ADRs and their rates, they need to further 20 stress the importance of actually reporting incidents of ADRs so both doctors and patients can be made more aware of their prevalence. It is noted that the actual rates of ADRs in retail-chain pharmacies vary between 1.8% and 6.7% depending on the study conducted (Bond and Raehl, 2006, Pirmohamed, 2004, Onder, et al, 2008, Lazarou, 1998. While these numbers may seem small, they still mean that up to 1 in 16 patients will experience some kind of adverse drug reaction after receiving and taking their drugs from the retail pharmacy.…”
Section: Decrease In Pharmacist-patient Counseling and Relationship Tmentioning
confidence: 99%
“…First, automation in the form of script-filling machinery and electronic systems such as computer databases is prevalent in corporatized pharmacies (Bush et al, 2008). Corporatization is also associated with other changes including increases in efficiency of workflow, reduced staffing and increases in ADR rates (Green et al, 2011, Onder et al, 2008. 'Compliance' otherwise referred to as 'adherence' or 'concordance' is defined generally by the World Health Organization (WHO) as: "The extent to which a person's behavior -taking medications, following a diet, and/or executing lifestyle changes, corresponds with agreed recommendations from a health care provider" (WHO, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Data were analyzed by binary logistic regression applying stepwise backward selection using presence or absence of ADEs as the dependent variable. In the primary analysis, the independent variables included age, sex, number of prescribed medications, Charlson Comorbidity Index [28] and dementia diagnosis (possible or probable Alzheimer's disease, other dementing illness, mild cognitive impairment), which have previously been shown to be independent predictors of ADEs [32][33][34] . Additional independent variables entered into the model included MMSE (total score), baseline use of NHPs, years of education, and race (Caucasian or non-Caucasian).…”
Section: Discussionmentioning
confidence: 99%